Pediatric Vaginal Discharge - Fitria Salim; Sitti Hajar (The International Journal of Tropical Veterinary and Biomedical Research, 2017)
Vaginal discharges are commonly seen in the pediatric population, approximately more than 50% of all pediatric genital complaints. Normal vaginal secretion is usually thin, and clear to white with a variable amount, while malodorous, abnormal consistency of vaginal discharge accompanied by blood, pain, pruritus, or dysuria is usually pathologic. Many factors can cause vaginal discharge such as anatomy of genital area that more susceptible to inflammation and infection, numerous organisms that including those associated with the sexually transmitted diseases or child sexual abuse, also mechanical and chemical substances, as well as poor hygiene. Recurrent vaginal discharge can be very distressing to children, especially if associated with discomfort and the most common cause is vulvovaginitis. The management of vaginal discharge is based on underlying causes, either by initiating proper therapeutic or teaching the children about good hygiene.